Could Buildings Finishing Materials Contribute on Limiting Diffusion of Infections Transmitted by Users during their Activities in High-Used Infrastructures - Zaid A. O. Al. Deek, Lama Z. Al. Khateeb (International Journal of Advanced Science and Technology, 2020)
This study analyses how could buildings finishing materials contribute to limiting diffusion of infections transmitted by users during their activities in high-used infrastructures as hospitals, supermarkets, malls, and others. The aim of this study is to find materials that can be disinfected with the activation of some chemical and physical properties using broad range agents such as the sun or artificial light, water, and air. The activation of temporary surface proprieties of building materials and furniture’s as the level of acidity, ionization and other self-cleaning capacities by the broad range agent’s that aims to guarantee a total environmental disinfection that could be adapted easily and automatically. The expected results could limit diffusion of infections contributing on the limitation of epidemics with sustainable and affordable modes.